The Efficacy of School Inspection and the Quality Teaching-Learning of Students in Lower Secondary Schools in Uganda - Busingye, John (Advances in Social Sciences Research Journal, 2020)
The study evaluated the efficacy of school Inspection upon quality teaching/learning in lower secondary Schools. The study targeted a population of 280 participants selected from twenty (20) schools with a sample size of 203 participants that was investigated. Questionnaires were the main data collection tool used. The study findings show that the geographical location of some schools, lack of enough finances to carry out inspection, bad weather conditions, heavy work load of duties by district inspector of schools and education officers. The study concluded that district education officers and inspector of schools were vital in the teaching learning processes. The study commends that there is need for excellent working relationship between the inspection team and classroom teachers through formal meetings to high light on the progress and challenges related to teaching/learning outcomes. The study further commends government to increase the budget allocated to lower secondary school inspection so as to inspire the inspection activities to be carried out as planned in the education sector.